The role of aldosterone in the pathogenesis of diabetic retinopathy - Liu, Kangcheng; Zou, Hua; Fan, Huimin; Hu, Hanying; Cheng, Yanhua; Liu, Jingying; Wu, Xiaojian; Chen, Bolin; You, Zhipeng (Frontiers in Endocrinology, 2023)
Aldosterone, as a mineralocorticoid of adrenal origin, has effects that are not limited to the urinary tract. As an important regulator in Vasoactive hormone pathways, aldosterone may play an effect in the pathogenesis of diabetic retinopathy (DR) through the regulation of oxidative stress, vascular regulation, and inflammatory mechanisms. This implies that mineralocorticoids, including aldosterone, have great potential and value for the diagnosis and treatment of DR. Because early studies did not focus on the intrinsic association between mineralocorticoids and DR, targeted research is still in its infancy and there are still many obstacles to its application in the clinical setting. Recent studies have improved the understanding of the effects of aldosterone on DR, and we review them with the aim of exploring possible mechanisms for the treatment and prevention of DR.